Identification of ecosystem services in communities associated with three Marine Areas of Responsible Fishing, Golfo de Nicoya, Costa Rica - Umaña Blanco, Valeria (2021)
Ecosystem services are fundamental for the survival of the human being and their recognition by the communities constitutes a first step towards their sustainable use. This paper analyzed the identification of ecosystem services by communities linked to three Marine Areas of Responsible Fishing in Golfo de Nicoya, Costa Rica, as a contribution to the definition of productive alternatives directed to reduce the pressure of the fishing activity in the area and improve the socioeconomic development. For this, a survey was applied in the surrounding communities of the following Marine Areas of Responsible Fishing: Isla Venado, Isla Caballo and Paquera-Tambor. In general, 90% of the people involved in the survey claimed to get ecosystem services and this represents an opportunity to make rational use of such services. The services mostly mentioned by people from these communities reflect an almost exclusive recognition of provisioning services, particularly the supply of fishery products. It will be valuable to focus on new, more sustainable forms of production, as well as strengthening education and awareness of the significance of ecosystem services in order to guarantee the integral well-being of people in the communities associated with Marine Areas of Responsible Fishing.